Peningkatan Ketrampilan Kelompok Wanita Tani Desa Mlese Melalui Pelatihan Tehnik-Tehnik Pertanian Terpadu - kartinah, kartinah (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This service activity is part of a series of community services in Mlese Village, Klaten Regency, Central Java. The potential of this village includes the availability of a fairly large agricultural land but has not been optimally utilized. So far, it has only been planted with rice. In line with the village program in 2023-2024, namely forming an Agroedutourism Village, by carrying out three fields in it, namely: Agriculture, Education, and Tourism. In order to realize all three, training, workshops, and mentoring are gradually held for the Mlese village community, especially for the Women Farmers Group. All members of KWT Mlese village followed the whole series seriously, so that 90% of the members were able and had applied the knowledge gained from the resource persons. This can be seen by starting to see plants of long beans, chilies, cassava, tomatoes, cobbage.